A study of the design methodologies of RF CMOS mixers for low-IF receivers - Mayuga, Gian Paolo T. (2009)
In this thesis, the investigation of design methodologies implemented for fully-integrated RF CMOS down-conversion mixers is presented. In order to satisfy the design constraints, design methodologies that dictates upon the performance parameters specifically (1) conversion gain, (2) noise figure and (3) linearity were explored and utilized. This has been done by illustrating a complete design process for the single-balanced current-switching mixer to achieve the desired parameters.Fully-integrated mixer test circuits, including the reference circuit of which performance of other circuits were compared to, were implemented and fabricated. Analysis and simulation results show that depending on the desired mixer performance, the proper design methodology can be chosen to fulfll the performance desired for application needs. The designs have been fabricated in 0.25 um standard CMOS technology.